METODE LISAN SEBAGAI SISTEM PEDAGOGIS KULTURAL: PEMBELAJARAN SENI KARAWITAN DAN PEDALANGAN DI SANGGAR BALADEWA SURABAYA - Tatas Aglis Budi Jatmiko; Anbie Haldini Muhammad; Indar Sabri; Welly Suryandoko (STKIP Subang, 2026)
Amidst the dominance of text-based formal education and the acceleration of digitalization, the oral transmission of traditional arts knowledge tends to be marginalized. Yet this method plays a vital role in preserving authenticity and cultural context in traditional arts learning. This study aims to describe the implementation patterns of the oral method, identify its pedagogical-cultural components, and analyze its contribution to student competency at Sanggar Baladewa Surabaya. A descriptive-analytical qualitative approach was employed. Data were collected through participatory observation across eight training sessions, semi-structured interviews, and documentation studies involving teachers, senior members, and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2020), comprising: (1) data condensation, (2) selective dialogue, (3) data presentation, and (4) conclusion drawing. The study reveals that the oral method is implemented through four main patterns: (1) direct verbal instruction and spontaneous correction, (2) oral naming of patterns and terms, (3) phrase repetition via call-and-response mechanisms, and (4) contextual narrative and symbolic analogy. This method functions as an adaptive learning scaffold while simultaneously serving as a medium for transmitting cultural values, etiquette, and artistic philosophy as reflected in the concept of Manunggaling Kawula Gusti. Its contribution is evident in stable procedural memory retention, increased improvisation confidence, and the internalization of collective identity. This study concludes that the oral method is not merely an alternative technique, but a living and relevant cultural pedagogical system worthy of integration into modern arts education curricula.